Handling Solutions for Electronic Waste (E - Waste) in Indonesia - Dedy Suprayogi (Al-Ard: Jurnal Teknik Lingkungan, 2016)
Any changes always take effect to the environment either positive or negative, it is no exception developments in technology. In addition to bringing benefits to the human development, technology has always had a negative impact, actually thrash or waste from obsolete technology as the results of the process productions or side product. The mobile phones waste is one of the electronic waste that need to be awareness. Electronic waste processing in particular mobile phones as one of the new problems in the waste management, and it will be an ice mountain problem for developing countries because generally they have limited technology, insufficiency of financial and lack of human resources in the management of electronic waste that electronic trash left to accumulate for granted. Indonesia as a developing country need to strengthening regulatory, economic support and technology transfer of electronic waste management from developed countries to suppress pollution caused by electronic waste disposal carelessly.